2021
DOI: 10.1002/aelm.202100893
|View full text |Cite
|
Sign up to set email alerts
|

Recent Progress of Solution‐Processed Copper‐based p‐Channel Thin‐Film Transistors

Abstract: unstoppable march of today's technology, it is of great demand to develop alternative and inexpensive processing technologies for fabricating high-performance p-channel TFTs. Ink-jet printing, by which semiconductor materials can be deposited on flexible substrates such as polymer films or paper, is one such promising alternative. [5][6][7] However, due to the difficulty in formulating the printable ink precursors of inorganic materials compared to organic ones, printing technology is generally uncommon in met… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
0
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 93 publications
(185 reference statements)
0
0
0
Order By: Relevance
“…Inorganic transparent semiconductors are required in solar cells and other devices, like thin-film transistors (TFTs), light-emitting diodes (LEDs), and smart sensors [1][2][3][4][5][6]. Solar cells produce electric power from solar energy and are a promising option to meet the energy demand with high efficiency.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Inorganic transparent semiconductors are required in solar cells and other devices, like thin-film transistors (TFTs), light-emitting diodes (LEDs), and smart sensors [1][2][3][4][5][6]. Solar cells produce electric power from solar energy and are a promising option to meet the energy demand with high efficiency.…”
Section: Introductionmentioning
confidence: 99%
“…Hence, there is a considerable need to find materials that possess low resistivity for electrical conduction and high transparency for solar cells, TFTs, and LEDs. This has led to extensive research on compounds, such as In 2 O 3 , ZnO, SnO 2 , and complex oxides [4,[15][16][17][18][19]. Despite extensive research, most of these materials discovered thus far display n-type conductivity, and there are few viable choices for p-type materials with high hole carrier density and/or mobility.…”
Section: Introductionmentioning
confidence: 99%
“…Among the different candidates, a transparent p-type semiconductor copper iodide (CuI), including I 5p orbital with large spatial spread and displaying high intrinsic hole mobility over 40 cm 2 V –1 s –1 , has great potential to fabricate high-performance p-channel TFTs . Usually, the CuI film used in p-channel TFTs is easily obtained by solution methods at low postannealing temperatures (<150 °C). , Liu et al obtained the first solution-processed CuI TFT with a low on/off current ( I ON / I OFF ) ratio of 5 × 10 2 at room temperature . The low I ON / I OFF ratio of CuI TFT is mainly derived from the lower formation energy of Cu vacancies, resulting in excessive holes formation in CuI film. , Kwon et al reported CuI TFT with optimized morphology based on high- k ( k ∼ 108) sodium-embedded alumina (Na-doped Al 2 O 3 ), showing a hole mobility of 21.6 cm 2 V –1 s –1 and a high I ON / I OFF ratio of 10 5 .…”
Section: Introductionmentioning
confidence: 99%